Deterioration of pre-existing hemiparesis brought about by subsequent ipsilateral lacunar infarction. Issue 8 (21st July 2003) - Ago, T; Kitazono, T; Ooboshi, H; Takada, J; Yoshiura, T; Mihara, F; Ibayashi, S; Iida, M
Abstract : Mechanisms of post-stroke recovery are still poorly understood. Recent evidence suggests that cortical reorganisation in the unaffected hemisphere plays an important role. A 59 year old man developed a small lacunar infarct in the left corona radiata, which then caused marked deterioration in a pre-existing left hemiparesis that had resulted from an earlier right putaminal haemorrhage. Functional magnetic resonance imaging showed that the paretic left hand grip activated the ipsilateral left motor areas, but not the right hemispheric motor areas. This suggests that partial recovery of the left hemiparesis had been brought about by cortical reorganisation of the left hemisphere and intensification of the uncrossed corticospinal tract. The subsequent small infarct may have damaged the uncrossed tract, thereby causing the pre-existing hemiparesis to deteriorate even further.